Analisis Hasil Pembentukan Kayu Billiard Menggunakan Mesin Bubut dan Mesin Router - Relvin; Rosehan, Rosehan; Lubis, Muhammad Sobron Yamin (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2024)
Making billiard sticks is a production process that requires high precision to produce quality products. This research aims to analyze the comparative performance of various cutting tools in the turning process for making billiard sticks. Proper cutting tools are essential in the pool cue manufacturing industry to achieve precise and quality results. This research uses two types of processes: the turning and the routing machine processes. The turning process is carried out on rosewood/snorkelling (Dalbergia latifolia) woodworkpieces, which will be used as billiard sticks. This research aims to evaluate dimensional accuracy and production process time. The turning process is carried out by varying the cutting speed parameters and feed depth. This research focuses on optimizing lathes' use to produce stick dimensions that comply with international standards. The study showed that turning tapered wood in a lathe to make billiard sticks took longer (376.2 seconds) than using a router machine (225.6 seconds).